2016
DOI: 10.1128/aem.03355-15
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the Salmonella enterica KdgR Regulon to Persistence of the Pathogen in Vegetable Soft Rots

Abstract: bDuring their colonization of plants, human enteric pathogens, such as Salmonella enterica, are known to benefit from interactions with phytopathogens. At least in part, benefits derived by Salmonella from the association with a soft rot caused by Pectobacterium carotovorum were shown to be dependent on Salmonella KdgR, a regulator of genes involved in the uptake and utilization of carbon sources derived from the degradation of plant polymers. A Salmonella kdgR mutant was more fit in soft rots but not in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Having previously reported that kdgR alone is not responsible for the growth of S . Typhimurium 14028 in soft-rotted tomatoes ( 24 ) and in light of the fact that the starch-scavenging hypothesis was proven null, we performed a high-throughput assay in order to identify the full complement of genes responsible for this interaction. Transposon sequencing (Tn-Seq) has become an important tool for untangling complex metabolic networks in Salmonella spp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Having previously reported that kdgR alone is not responsible for the growth of S . Typhimurium 14028 in soft-rotted tomatoes ( 24 ) and in light of the fact that the starch-scavenging hypothesis was proven null, we performed a high-throughput assay in order to identify the full complement of genes responsible for this interaction. Transposon sequencing (Tn-Seq) has become an important tool for untangling complex metabolic networks in Salmonella spp.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we established that the deletion of the kdgR gene, which codes for a repressor of cell wall degradation and uptake of monomers and dimers resulting from the plant cell wall breakdown, was beneficial to the growth of S. enterica serovar Typhimurium strain ATCC 14028 ( S . Typhimurium 14028) in soft rot ( 24 ). However, further investigation of the KdgR regulon did not offer a conclusive explanation for its role in the ability of Salmonella spp.…”
Section: Introductionmentioning
confidence: 99%
“…One of these mutations mapped to kdgR (9), a transcriptional regulator that modulates uptake of distinct carbon sources. Intriguingly, the KdgR regulon favors persistence of serovar Typhimurium in vegetable soft rots in association with defined phytopathogens such as Pectobacterium carotovorum (77). This role in persistence was linked to increased uptake of carbon sources derived from pectin degradation and utilization of the Entner-Doudoroff pathway, both regulated by KdgR (77).…”
Section: The Scv As a Suitable Niche To Prolong Host Infection In A Nmentioning
confidence: 99%
“…Intriguingly, the KdgR regulon favors persistence of serovar Typhimurium in vegetable soft rots in association with defined phytopathogens such as Pectobacterium carotovorum (77). This role in persistence was linked to increased uptake of carbon sources derived from pectin degradation and utilization of the Entner-Doudoroff pathway, both regulated by KdgR (77). Mammalian cells do not produce pectin, so it is tempting to speculate that the action of KdgR in intracellular serovar Typhimurium is related to the hydrolysis and product utilization of some yet unknown polysaccharide.…”
Section: The Scv As a Suitable Niche To Prolong Host Infection In A Nmentioning
confidence: 99%
“…Although human pathogens may benefit from the release of substrates from damaged cells in plant lesions ( Aruscavage et al, 2010 ; Kyle et al, 2010 ; Goudeau et al, 2013 ; George et al, 2016 ), physicochemical conditions resulting from the injury per se and from the plant defense response to wounding or infection may also contribute to the outcome of a contamination event at the site of injury. Our transcriptomic studies previously revealed that in addition to responding to oxidative and antimicrobial stress in romaine lettuce leaf lysate and in cut leaf tissue, EcO157 mounted a response to osmotic stress by upregulation of the betA and betB genes for GB synthesis while the otsBA genes for production of the osmoprotectant trehalose were strongly downregulated ( Kyle et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%